Control of an Industrial-type Multicomponent Crude Distillation Column using Biggest Log Modulus Tuning. (2020) - Abraham, Anuj; Muralidharan, Ganesh; Pappa, N.
Abstract: This paper is mainly focused on the Multi-Input-Multi-Output (MIMO) control design of an industrial-type multicomponent crude distillation column with 5 sidestreams. The mathematical model of a multicomponent crude distillation column was investigated in Ganesh, M et al. (2016), which aimed at predicting the concentration (mole fraction) and control of the concentration of any product taken out from the column. The VLE values on individual trays are obtained by reverse calculation of the Thomas algorithm and the composition on each tray are obtained. A transfer function model is obtained with five inputs namely Liquid flow rate, Vapor flow rate, SRK flow rate, LDO flow rate, and HDO flow rate and five outputs which are concentrations of the Whole Naphtha, SRK, LDO, HDO, and AR. This transfer function model is used to obtain the steady state matrix and the RGA analysis is performed to solve the pairing issues of the complex multivariable system. A PI controller is then designed by using BLT tuning which provides standard tuning methodology. This procedure helps at arriving standard tuning values with less computational effort.